A population pharmacokinetics analysis assessing the exposure of raltegravir once‐daily 1200 mg in pregnant women living with HIV. (25th January 2021) - Bukkems, Vera E.; Post, Teun M.; Colbers, Angela P.; Burger, David M.; Svensson, Elin M.
Abstract: Once‐daily two 600 mg tablets (1200 mg q.d.) raltegravir offers an easier treatment option compared to the twice‐daily regimen of one 400 mg tablet. No pharmacokinetic, efficacy, or safety data of the 1200 mg q.d. regimen have been reported in pregnant women to date as it is challenging to collect these clinical data. This study aimed to develop a population pharmacokinetic (PopPK) model to predict the pharmacokinetic profile of raltegravir 1200 mg q.d. in pregnant women and to discuss the expected pharmacodynamic properties of raltegravir 1200 mg q.d. during pregnancy based on previously reported concentration‐effect relationships. Data from 11 pharmacokinetic studies were pooled ( n = 221). A two‐compartment model with first‐order elimination and absorption through three sequential transit compartments best described the data. We assessed that the bio‐availability of the 600 mg tablets was 21% higher as the 400 mg tablets, and the bio‐availability in pregnant women was 49% lower. Monte–Carlo simulations were performed to predict the pharmacokinetic profile of 1200 mg q.d. in pregnant and nonpregnant women. The primary criteria for efficacy were that the lower bound of the 90% confidence interval (CI) of the concentration before next dose administration (Ctrough ) geometric mean ratio (GMR) of simulated pregnant/nonpregnant women had to be greater than 0.75. The simulated raltegravir Ctrough GMR (90% CI) was 0.51 (0.41–0.63), hence not meeting the primary target for efficacy. Clinical data from two pregnant women using 1200 mg q.d. raltegravir showed a similar Ctrough ratio pregnant/nonpregnant. Our pharmacokinetic results support the current recommendation of not using the raltegravir 1200 mg q.d. regimen during pregnancy until more data on the exposure‐response relationship becomes available.